European General Practice Research Network (EGPRN). (March 2013) - Van Royen, Paul; Rees, Charlotte E.; Groenewegen, Peter; Van Bergen, Jonathan; Philips, Hilde; Remmen, Roy; Bombeke, Katrien; Mortelmans, D.; Symons, L.; Debaene, L.; Schol, S.; De Winter, B.; et al.
<x xml:space="preserve">Abstract</x> Abstracts from the EGPRN meeting in Antwerp, Belgium, 18th – 21st October, 2012. Theme: 'Research on Patient-centred Interprofessional Collaboration in Primary Care'